SOSIALISASI BANK SYARIAH KEPADA MASYARAKAT KELURAHAN TIMBANGAN KOTA PADANGSIDIMPUAN - Nasution, Hamni Fadlilah; Zulaika Matondang (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
This community service activity is carried out so that people have an understanding of Islamic banking. This service activity is carried out for people who live in the Timbangan Village, North Padangsidimpuan District. This activity was carried out in 3 stages. The first stage is the preparatory stage, the preparation is carried out by asking permission from the Kelurahan where the service is carried out. The second stage is pre-socialization, namely the service volunteer team conducts interviews with the community. The third stage is the socialization stage, carried out by interviews and questions and answers with the community. The results of the activity show that there are still many people who are not familiar with Islamic banks, from this activity the community becomes aware of the existence of Islamic banks, 2) The community understands the concepts in Islamic banks, 3) This activity is a forum for increasing the knowledge and understanding of the community about Islamic banks, which Prior to this activity, most people considered Islamic banks and conventional banks the same and 4) The community expressed an interest in conducting transactions at Islamic banks after gaining knowledge and understanding of Islamic banks.